Detectorists. Series 3 [videorecording (DVD)] - Crook, Mackenzie, 1971-; Crook, Mackenzie, 1971-; Jones, Toby, 1966-; Stirling, Rachael, 1977- (Acorn Media Enterprises, 2018)
Andy and Lance continue to pursue their shared hobby of metal detecting searching the Essex countryside for treasure while navigating the challenges of their personal lives.